Hal-Hal Yang Ada Hubungan Dengan Gagal Jantung Kongestif Pada Penderita Di Beberapa Lokasi Di Wilayah Asia Dan Amerika Pada Periode Tahun 2008 Sampai Dengan Tahun 2021 - Nurismayanti, Aulia; Sartika, Suriana Dwi; Ramadani, Andi Anissa (Fakultas Kedokteran Universitas Bosowa, 2024)
Congestive Heart Failure (CHF) is a condition in which there is a structural or functional abnormality of the heart which causes the heart to fail to deliver oxygen throughout the body for fill the tissue needs by increasing filling pressure or its ability only if accompanied by an abnormal increase in diastolic volume. The purpose of this study was to find out things that have a relationship with congestive heart failure in patients in several locations in Asia and America in the period 2008 to 2021. The research method was an analytical research by processing the results obtained from nine scientific research journals with research design is a case-control. The results of the nine research journals analyzed showed that there was a relationship with congestive heart failure in several locations in Asia and America, there was a significant relationship between hypertension, diabetes mellitus, chronic kidney failure, and smoking on congestive heart failure with p-values <0.05. Meanwhile, there was no significant relationship between dyslipidemia and obesity with congestive heart failure with p-value > 0.05 in several locations in Asia and America. The conclusion of congestive heart failure in patients in several locations in Asia and America in the period 2008 to 2021 there was a significant relationship between hypertension, diabetes mellitus, chronic kidney failure and smoking on the incidence of congestive heart failure.